Pengetahuan Investasi, Modal Minimum Investasi, Pelatihan Pasar Modal, Motivasi Investasi, Return Investasi dan Persepsi Risiko dalam Minat Mahasiswa Berinvestasi - Putra, Pramundita Risna; Muharam, Harjum (Ekonomis: Journal of Economics and Business, 2025)
This study aims to obtain empirical evidence regarding the influence of minimum investment capital, investment motivation, investment knowledge, investment risk, capital market training, and investment returns on investment interest in students in Semarang. Respondents consisted of 122 active students who met the research requirements. The data collection method was through questionnaires distributed to students at universities who met the research criteria and had undergone education or training in capital markets. Data analysis used in this study used multiple linear regression. The results showed that investment knowledge, minimum investment capital, capital market training, investment motivation, and investment returns had a positive and significant effect on student investment interest. Only the variable of investment risk perception had a negative effect on student investment interest in Semarang.